Contrast-enhanced magnetic resonance angiography for monitoring an embolized renal artery aneurysm: A case report and literature review. Issue 11 (November 2022) - Yang, Xin-Zhi; Li, Peng-Yu; Zhang, Bi-Hui; Yan, Zi-Guang; Niu, Guo-Chen; Yang, Min
This case report describes a 69-year-old male patient with a renal artery aneurysm that was followed up with contrast-enhanced magnetic resonance angiography at 8 months after coil embolization treatment. Due to the disappearance of residual lumen with few metal artifacts, the therapeutic effect was satisfactory. At present, the indications for the treatment of renal artery aneurysms are still controversial and there are very few reports of postembolization images of renal artery aneurysms, with no criteria for reintervention and few reports for monitoring the embolized aneurysms. Further reports and research are still needed for the treatment of this rare disease.